Socialization of Public Health Literacy through Noun Phrase Translation in Medical Texts: Sosialisasi Literasi Kesehatan Masyarakat melalui Terjemahan Noun Phrase pada Teks Medis - Margaret Stevani; Ikhwan Mahfud Hidayat (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
English as a lingua franca required an in-depth understanding of the translation of noun phrases in medical terminology due to the complex nature of noun phrases and involving explanatory words, resulting in a lack of understanding regarding the equivalence of meaning in English. The focus of this community service was to improve understanding of noun phrases in medical texts by applying translation analysis techniques which include translation shifts at the unit, structure, category and intra-system levels. Qualitative data from sentences in English medical textbooks and their translations into Indonesian were used as a basis for analysis through content analysis methods and focus group discussions (FGD) to understand the process of changing meaning in translation. The research sample involved 14 undergraduate students of Pharmacy and D-III Midwifery semester V at STIKes Mitra Husada Medan, North Sumatra. The results of this community service contribute to increasing public health literacy, especially among students in the health sector, thereby enabling collaboration between two fields of science that mutually contribute to sustainable development.